Effects of thermal and mechanical activation methods on compressive strength of ordinary Portland cement-slag mortar - Sajedi, Fathollah; Razak, Hashim Abdul (Elsevier, 2011)
Activation methods and curing regimes have crucial effects on the strength of mortars and concretes. The objective of this investigation is to examine the early and later compressive strength of activated ordinary Portland cement (OPC)-ground granulated blast-furnace slag (GGBFS) mortars and identify the most effective activation technique. The methods of activation used were thermal, mechanical and thermal-mechanical combined. Two curing regimes were adopted and five groups of mortars were prepared. It was observed that OPC-GGBFS mortars have greater sensitivity to OPC mortars against the curing regimes. However, the study revealed that there was no particular activation method which when used gave the best results for both early and later strengths and did not cause strength loss. It also proved that the most effective activation method for early strength is a combination of both the thermal and mechanical, while for later strengths, none of the activation methods was recommended. Â© 2010 Elsevier Ltd.